Assessment of association among the component traits and their effects on the seed yield in Cluster bean [Cyamopsis tetragonal (L). Taub.] - Kapil Bishnoi; Vijay Prakash; A.K. Sharma; Ravinder Kumar (Annals of Agricultural Research, 2023)
An experiment was carried out to determine the relationship among the component traits and their direct and indirect effects on the seed yield using forty diverse genotypes of cluster bean, collected from Rajasthan Agricultural Research Institute, Durgapura and Agriculture Research Station, Bikaner during Kharif 2019 at Research Farm, SKRAU, Bikaner. The experimental material was raised in Randomized Block Design with three replicates and observations were recorded for twelve seed-related traits. Certain component traits under consideration, such as number of branches per plant, number of clusters per plant, number of pods per plant and biological yield per plant showed strong positive correlation with seed yield per plant. Path coefficient analysis concluded that biological yield per plant, 100-seed weight, number of branches per plant and pod length all had significantly positive direct effect on seed yield per plant. Hence, these traits can be taken as the useful criteria for the improvement of yield and its contributing traits in cluster bean improvement programmes.